Impact of Foreign Direct Investment on Indian Economy - Chauhan, Mukesh (Gyan Management Journal, 2016)
One of the most striking developments during the last two decades is the spectacular growth of FD! in the global economic landscape. This unprecedented growth of global FD! in 1990 around the world make FD! an important and vital component of development strategy in both developed and developing nations and policies are designed in order to stimulate inward flows. In fact, FD! provides a win -win situation to the host and the home countries. Both countries are directly interested in inviting FD!, because they benefit a lot from such type of investment. The ’home’ countries want to take the advantage of the vast markets opened by industrial growth. On the other hand the ’host’ countries want to acquire technological and managerial skills and supplement domestic savings and foreign exchange. Moreover, the paucity of all types of resources viz. financial, capital, entrepreneurship, technological know- how, skills and practices, access to markets- abroad- in their economic development, developing nations accepted FD! as a sole visible panacea for all their scarcities. Further, the integration of global financial markets paves ways to this explosive growth of FD! around the globe. The growth of FD! is tremendous in India it was only 256 crores in 1948 which reached to 147518 crores in 2014. Further, the explosive growth of FD! gives opportunities to Indian industry for technological up gradation, gaining access to global managerial skills and practices, optimizing utilization of human and natural resources and competing internationally with higher efficiency. Most importantly FD! is central for India’s integration into global production chains which involves production by MN Cs spread across locations all over the world. The present paper has been aimed at to find out the trends and patterns of flow of FD!, to assess the determinants of FD! inflows and to evaluate the impact of FD! on the Economy.